Scoring effiency and final outcomes of handball matches - Vuleta, D.; Milanovic, D.; Sertic, H. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
continuous game flow (set defence - fast break - set attack - transition to defence) sustained by the relations of co-operation (among teammates) and confrontation (among rivals) reign. Research on performance parameters should enable a prognosis of the final outcome of handball matches. The goal of the study is to determine the relationships between variables of shooting for a goal and final outcomes of 38 matches of the 2000 Men's Handball EC. Methods The sample of manifest variables (12): 7m throws - made and missed (7MTM & 7MTmiss); 6m-centre shots - made and missed (6MCSHM & 6MCSHmiss); wing shots - made and missed (WSHM & WSHmiss); field shots (back-court) - made and missed (FSHM & FSHmiss); fast break shots - made and missed (FBSHM & FBSHmiss); breakthrough shots - made and missed (BTSHM & BTSHmiss). The criterion variable: a binary match outcome - victory (WINN) or defeat (DEF). Basic statistics (Table 1) was computed and the predictive power of scoring variables (Table 2) was determined using multiple regression analysis (STATISTICA 5.0). Discussion/Conclusion Almost half of all the shots performed (44.61%) were executed from the back-court players' positions (field shots). The winning teams were considerably more efficient in field shots and in 7m throws than the defeated ones - (43.20%) and (76.53%) as compared to (32.52%) and (65.76%), respectively. It can be concluded that the average of 25 goals scored per game by one team, or a goal scored every 1.2 minutes by either of the rivals in a match characterised the scoring efficiency of the observed top-level male teams. The coefficient of multiple correlation (.71) is statistically significant and leaves no doubt that success or victory in handball can be predicted from the variables of shooting for a goal. Namely, they have explained 50% of the common variance of diverse ways of closing attack actions, both made and missed, and of the binary defined final match outcomes. Four predictor variables have a significant (.99) influence on the playing performance of the observed sample: FSHM (0.53), 6MCSHM (0.39), FSHmiss (- 0.38), and 7MTmiss (- 0.31). Besides the listed, the following two variables were significant at the .95 level: WSHM (0.27) and FBSHM (0.25). It is important to stress here that the variables of unsuccessful shots for a goal have a negative sign, whereas the variables of successful shots have a positive sign. The winning teams had more successful field shots, 6m-centre shots and wing shots, and fewer unsuccessful 6m-centre and field shots and 7m throws. Scoring efficiency from a distance and from the 6m line differentiates the successful teams (winners) from the unsuccessful (defeated) ones.